(untitled) (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : This research will be based in the background by a problem in the pineleng Sub-district office of the Regency of minahasa in the Government apparatus work competencies influence the villages that still have not contributed optimally. Therefore it is necessary the presence of the influence of good working competencies in order to improve the performance of government apparatus of the village. Thus it can be said that the Government apparatus village in the Pineleng does not yet have adequate competence in implementing village autonomy demands appropriate mandate Law No. 6 Year 2014 so it can certainly will affect their performance in achieving the goals and objectives of Government and the development of the village. Based on the results of the study as already expressed above, it needs to be given some advice, among other things: remembering the accomplishments of the Government apparatus performance village is still low, given the still weak influence aspects of formal education and training/skill performance against government apparatus apparatus village, partially, only factors factors that influence significant working experience terhada village government apparatus performance, meanwhile, simultaneously or together, all three of these factors (education , training and work experience) effect very significantly to the performance of the Government apparatus. Based on a summary of items 3 and 4 can be said that all the hypotheses put forward acceptable convincingly at once has justification of the underlying theories. Keyword : competencies, performance Government apparatus village